2015
DOI: 10.1371/journal.pone.0131207
|View full text |Cite
|
Sign up to set email alerts
|

Phenformin Induces Cell Cycle Change, Apoptosis, and Mesenchymal-Epithelial Transition and Regulates the AMPK/mTOR/p70s6k and MAPK/ERK Pathways in Breast Cancer Cells

Abstract: Breast cancer remains a world-wide challenge, and additional anti-cancer therapies are still urgently needed. Emerging evidence has demonstrated the potent anti-tumor effect of biguanides, among which phenformin was reported to potentially be a more active anti-cancer agent than metformin. However, little attention has been given to the role of phenformin in breast cancer. In this study, we reveal the role of phenformin in cell death of the MCF7, ZR-75-1, MDA-MB-231 and SUM1315 breast cancer cell lines. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
5
39
0
1
Order By: Relevance
“…ERK signaling pathway is important for regulating cell cycle by promoting cells from G1 phase to S phase [17]. Our results showed that baicalein blocked T24 cells in G0~G1 phase.…”
Section: Discussionmentioning
confidence: 51%
“…ERK signaling pathway is important for regulating cell cycle by promoting cells from G1 phase to S phase [17]. Our results showed that baicalein blocked T24 cells in G0~G1 phase.…”
Section: Discussionmentioning
confidence: 51%
“…AMP‐activated protein kinase (AMPK) is a serine/threonine protein kinase that maintains the production and consumption of ATP in most eukaryotic cells . AMPK is also involved in multiple cellular processes, including myocardial energy metabolism , cell cycle modulation , and regulation of endothelia and vasorelaxation . Studies have shown the widespread expression of AMPK in the heart, expression that is related to cardioprotective effects against myocardial ischemia‐reperfusion (I/R) injury .…”
Section: Introductionmentioning
confidence: 99%
“…mTOR regulates protein synthesis by integrating hormones, nutrients, amino acids, cell oxidative stress, and other signals, thereby modulating growth, proliferation, and apoptosis . p70S6K is known to promote cell growth and proliferation . Data from the present study showed that expression of PI3K protein was inhibited by nano TiO 2 , leading to reduction of AKT, p‐mTOR, and p‐p70S6K1, and a consequent increase in atretic follicles, retardation of oocyte growth, and POF in female mice.…”
Section: Discussionmentioning
confidence: 51%